2020
DOI: 10.3390/ijerph17124346
|View full text |Cite
|
Sign up to set email alerts
|

Incentive Mechanism and Subsidy Design for Construction and Demolition Waste Recycling under Information Asymmetry with Reciprocal Behaviors

Abstract: To solve information asymmetry, we adopted the principal-agent framework to design the incentive mechanisms between the remanufacturer and the collector in the construction and demolition (C&D) waste-recycling industry. By using the model of reciprocity, we analyzed how the entities’ behavioral motives affect their decisions in terms of the incentive mechanisms. The findings showed that the collector responds to their perception of the remanufacturer’s intentions. If the perception is positive, they will m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
(80 reference statements)
0
21
0
Order By: Relevance
“…Poor information management. Lack of information sharing and resulting information asymmetries is a widely discussed issue in C&DW reprocessing (Su et al, 2020). Due to weak information exchange mechanisms between demolition contractors and waste processors, demolition contractors are unaware of opportunities for DW recovery and specific requirements of DW flows for reprocessing.…”
Section: Inhibitors Of External Integration Across Dw Rlscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor information management. Lack of information sharing and resulting information asymmetries is a widely discussed issue in C&DW reprocessing (Su et al, 2020). Due to weak information exchange mechanisms between demolition contractors and waste processors, demolition contractors are unaware of opportunities for DW recovery and specific requirements of DW flows for reprocessing.…”
Section: Inhibitors Of External Integration Across Dw Rlscsmentioning
confidence: 99%
“…Within such a background, demolition contractors fail to recognize the value of recovering resources, which cannot be used for projects handled by them. Consequently, large volumes of DW are landfilled, whereas waste processors are faced with insufficient waste flows for reprocessing (Su et al, 2020). A gap in information exchange between secondary material users and upstream waste processors was also revealed through literature.…”
Section: Inhibitors Of External Integration Across Dw Rlscsmentioning
confidence: 99%
“…The existence of private information makes the distribution of AI among the entities, therefore our study relates to literature on the principal-agent theory, which is usually used in the design of incentive mechanisms (Su et al, 2020). According to Bovens et al (2014) the principal-agent theory encapsulates a rational choice modelling where the principal uses whatever actions to provide incentives for the agent to make decisions that the principal most prefers.…”
Section: Characteristics Of Asymmetric Informationmentioning
confidence: 99%
“…Laffont and Martimort (2009) proposed the theory of incentive based on the principal-agent frame-work, and stated that the need for proper incentive mechanisms appears when the principal hires an agent who has superior information. By testing principal-agent theory in buyer-supplier relationships, Su et al (2020) found that both ex ante and ex post forms of opportunism can explain the occurrence of moral hazard. Chang and Shen (2014) points out that to control the probability of AI occurring, the project owner can promote a collaborative bidding process, i.e., he can provide a fairtrading platform and thus strengthen the dissemination of information and knowledge.…”
Section: Characteristics Of Asymmetric Informationmentioning
confidence: 99%
“…The current practical results of CDW recycling in China are not satisfactory and one way to improve this condition is via the government's reward-penalty mechanism, which can effectively regulate the decision-making behavior of production and recycling units [24]. (1) In terms of the reward mechanism, government subsidies can increase the green behavior motivation of enterprises and can quickly improve the performance of the recycling supply chain [25]. Government subsidies can increase the profit of production and recycling units, so as to encourage them to participate in the supply chain with high-quality [26].…”
Section: Cdw Recycling In the Government's Reward-penalty Mechanismmentioning
confidence: 99%